DIGITAL LEADERSHIP AND ORGANIZATIONAL QUALITY CULTURE IN EDUCATION IN THE ERA OF DISRUPTION - Kartika Sari; Hartono, Hartono; Mukroji, Mukroji; Siswadi, Siswadi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2025)
The rapid development of digital technology in the Fourth Industrial Revolution era has encouraged the education sector to transform, especially in terms of leadership. The concept of Digital Leadership emerged as a strategic response to the need for adaptive, innovative, and competitive schools. This study uses a qualitative approach with a case study design (field research). Data were collected through direct observation and document study by reviewing relevant journal articles, books, and policy documents. This study aims to analyze digital leadership in strengthening a culture of quality in education in an era of disruption. The findings show that digital leadership is not only about the use of technology, but also about the ability of school leaders to integrate technology with strategic vision, foster a collaborative culture, and encourage continuous innovation. Digital Leadership plays a key role in improving management effectiveness, accelerating data-driven decision making, and strengthening collaboration between teachers, students, parents, and the community. The gaps in this study are as follows: 1) most previous studies on leadership have focused on conventional or transformational leadership, while studies discussing digital leadership in the context of education are still relatively limited. 2) Studies on digital leadership directly related to the culture of educational quality are still not comprehensive, especially at the implementation level in educational institutions. This research contributes to strengthening a culture of quality through improving learning quality, data-driven decision-making, and creating an open organizational climate oriented towards continuous improvement. Keywords: Digital leadership, Organizational culture, Innovation, Strategies